Efficacy and safety analysis of DEB-TACE for hepatocellular carcinoma with portal vein tumor thrombosis - Zhang, Yan; Hua, Yu-Yu; Wang, Li-Zhou (Discover. Oncology, 2025)
Purpose To investigate the efficacy and safety of drug-eluting beads transarterial chemoembolization (DEB-TACE) for hepatocellular carcinoma (HCC) with different types of portal vein tumor thrombosis (PVTT). Patients and methods Fifty patients with HCC complicated with PVTT from August 2016 to January 2021 were selected as subjects, all of whom were treated with DEB-TACE. According to PVTT classification, the patients were divided into type I ( n = 10), type II ( n = 16) and type III ( n = 24). The therapeutic efficacy was evaluated after 1 month of treatment, the changes in liver function indexes and tumor markers were statistically analyzed, and patients’ prognosis was evaluated. Results The three groups manifested no difference in disease response rate and disease control rate ( P > 0.05). Before DEB-TACE, albumin (ALB), total bilirubin (TBIL), alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP) in type III and type II groups were higher than those in type I group, and ALB and ALT in type III group were higher than those in type II group ( P < 0.05). After DEB-TACE, ALB, TBIL, ALT, and AST in type III and type II groups were lowered, as well as TBIL, ALT, and AST in type I group ( P < 0.05). Before DEB-TACE, α-fetoprotein (AFP) and PIVKA-II in type I group were the lowest, followed by type II and type III groups ( P < 0.05). AFP and PIVKA-II in patients with different PVTT types after DEB-TACE were lower than those before DEB-TACE ( P < 0.05). The survival rates of type I, type II, and type III groups were 70.00% (7/10), 31.25% (5/16), and 28.00% (7/24), respectively. The survival rates of type II and type III PVTT patients were lower than those of type I patients ( P < 0.05). No significant difference was shown in the survival rates of type II and type III PVTT patients ( P > 0.05). The median survival time of type II group was 17 months, which was higher than that of type III group (12.5 months) (the survival rate of type I group was higher than 50%, with no median survival time). Conclusion DEB-TACE has high clinical efficacy on HCC complicated with PVTT, which can improve liver function and suppress tumor markers. The survival rate of type II and type III PVTT patients after DEB-TACE is lower than that of type I PVTT patients.